Analisis Faktor - Faktor Yang Mempengaruhi Kinerja Pengelola Keuangan Daerah Kota Kupang: Studi Kasus Kantor Badan Keuangan Dan Aset Daerah - Apolonia Kudja; Petrus E. De. Rozari; Cicilia A. Tungga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine and analyze the factors that influence the performance of regional financial managers. This type of research is associative quantitative. The sampling technique used in this research was a saturated population and sample with a total of 30 respondents. The data used in this research is primary data obtained from questionnaires distributed directly to respondents who include employees at the Kupang City Regional Financial and Asset Agency office. Data analysis in this research used Multiple Linear Regression with the help of SPSS IBM 21 to process questionnaire data. The results of this research show that individual factors, leadership factors and system factors influence the performance of regional financial managers, while team factors and contextual factors do not partially influence the performance of regional financial managers. The analysis results obtained are, the calculated F value is 11,118 > Ftable 2,620. It is hoped that future researchers can develop research on the performance of regional financial managers using other variables. So as to add references in enriching knowledge and identifying other factors that are truly determinant elements of employee performance at work.